Sin Nombre Virus (SNV) Ig Isotype Antibody Response during Acute and Convalescent Phases of Hantavirus Pulmonary Syndrome - Pavel Bostik; Jorn Winter; Thomas G. Ksiazek; Pierre E. Rollin; Francois Villinger; Sherif R. Zaki; C.J. Peters; Aftab A. Ansari (Emerging Infectious Diseases, 2000)
Serum samples from 22 hantavirus pulmonary syndrome (HPS) patients were tested for Sin Nombre virus (SNV)-reactive antibodies. In the acute phase of HPS, 100% and 67% of the samples tested positive for SNV-specific immunoglobulin (Ig) M and IgA, respectively. Among the virus-specific IgG antibodies, the most prevalent were IgG3 (in 97% of samples), followed by IgG1 (70%), IgG2 (30%), and IgG4 (3%).